STANDARDS FOR SOCIAL WORK QUALIFICATIONS IN SOUTH AFRICA - Lombard, Antoinette; Grobbelaar, Margaret; Pruis, Santie (Social Work/Maatskaplike Werk, 2003)
South Africa has instituted a new education and training dispensation, with the core drivers being the South African Qualifications Authority (SAQA), National Standards bodies and Education and Training Quality Assurance bodies (Olivier, 1998:ix). The SAQA Act (1995) enables South Africa to develop its own integrated National Qualifications Framework (NQF) accompanied by a supporting quality-assurance system